Philosophy of science after feminism - Kourany, Janet A. (New York ; Oxford : Oxford University Press, 2010)
Providing not only a (descriptively and normatively) more adequate philosophy of science than what we have now, but also a more socially engaged and socially responsible philosophy of science, this book aims to promote a more socially engaged and socially responsible science.
Includes bibliographical references.
Description based on online resource; title from home page (viewed Dec. 17, 2010).
Keywords: Feminism and science; Women in science; Science -- Philosophy